2016
DOI: 10.1088/0953-2048/29/10/104001
|View full text |Cite
|
Sign up to set email alerts
|

Design of a conduction-cooled 9.4 T REBCO magnet for whole-body MRI systems

Abstract: A project on the development of REBa2Cu3O7−δ (REBCO) magnets for ultra-high-field magnetic resonance imaging (MRI) was started in 2013. Since REBCO-coated conductors feature high mechanical strength under tensile stress and high critical current density, use of REBCO coils would allow superconducting magnets to be made smaller and lighter than conventional ones. In addition, a conduction-cooled superconducting magnet is simpler to use than one cooled by a liquid helium bath because the operation and maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Rare earth barium copper oxide (REBCO) coated conductors (CC) have a tremendous potential for numerous applications such as fusion reactor magnets, high energy particle accelerators, generators, motors, superconducting magnetic energy storage, and magnetic resonance imaging over a broad temperature range of 4-77 K in high magnetic fields of 2-30 T, due to their high critical temperature, high irreversibility field and high critical current density [1][2][3][4][5][6][7][8][9][10]. Several research and development projects are ongoing to develop high-field magnets with insert coils of REBCO, due to its high current carrying capability in high background fields [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth barium copper oxide (REBCO) coated conductors (CC) have a tremendous potential for numerous applications such as fusion reactor magnets, high energy particle accelerators, generators, motors, superconducting magnetic energy storage, and magnetic resonance imaging over a broad temperature range of 4-77 K in high magnetic fields of 2-30 T, due to their high critical temperature, high irreversibility field and high critical current density [1][2][3][4][5][6][7][8][9][10]. Several research and development projects are ongoing to develop high-field magnets with insert coils of REBCO, due to its high current carrying capability in high background fields [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In Axi-FEM, currents in the axial component are neglected at the REBCO tape ends. And, it is impossible to consider the spiral pancake-winding structure and the inductive current by the time-varying axial field in (2). However, in [24], Mataira, et al have proposed a method to consider the spiral pancake-winding structure and the no-insulation (NI) winding based on the H-formulation.…”
Section: Axisymmetric Fem (Axi-fem)mentioning
confidence: 99%
“…N recent years, higher magnetic fields are required for higher performance in various fields: medicine (magnetic resonance imaging; MRI) [1]- [3], pharmacy (nuclear magnetic resonance; NMR) [5], particle accelerators [5], [6], and fusion devises [7], [8]. In 2019, it was reported that an insert magnet called "LBC3" wound with Rare-Earth Barium Copper Oxide (REBCO) coated conductor (CC) generated 14.4 T inside a 31.1-T resistive background magnet [9].…”
Section: Introductionmentioning
confidence: 99%